PENGEMBANGAN INSTRUMEN TES TIPE PILIHAN GANDA DALAM EVALUASI HASIL BELAJAR SISWA PADA KONSEP SEL TINGKAT SEKOLAH MENENGAH ATAS - Maulida Maulida; Syarifah Farissi Hamama (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to obtain a multiple choice type test instrument that conforms to the standard standards for cell material in high school biology subjects. This research was conducted from February to April 2014. The method used was a formative research type development method with a multiple choice test of 100 test items. The research subjects used were 43 students. Tests that were compiled and validated by a team of experts were given to the research subjects, then the data obtained were analyzed using the formula for difficulty level, different tests (different power), the effectiveness of the trickster, validity, and reliability. The results showed that the number of valid test items was 70 test items and had a high category of reliability. From the results of this study, it can be concluded that the test items developed have met the good test criteria, this is based on the categories in which all the requirements have been fulfilled.